Design of Student's Character Assessment Instruments in Industrial Work Culture at Aceh Vocational - Arhamni Hamid; Zahari Supaian; Anwar Ramli; Anisaturrahmi; Mutia Fariha; Rini Sulastri (Universitas Serambi Mekkah, 2024)
The character of Industrial Work Culture is universal, so it can be adopted to be applied to vocational education institutions as a basic thing so that later when students enter industry they will find several similar characteristics that students must already have. This study aims to realize a development design (blueprint) in instrument development. This investigation aims to produce an instrument that can be used to develop and measure the industrial work culture character of vocational students, especially those in Aceh. So far, the development of industrial work culture character has been mandated to be implemented by the Indonesian government. The theoretical basis of this study is the theory of Kartwohl and Bloom (1956). The affective domain is a domain related to attitudes, values, feelings, emotions, and stages of acceptance or rejection of an object in teaching and learning activities. Affective assessments need to be carried out in the same way as cognitive assessments, so students must have character competencies that can be measured like cognitive competencies. The affective domain is divided into five categories, namely: Receiving or Attending, Responding, Valuing, Managing, Characterization. The affective domain requires measurement tools like the cognitive domain so that students' affective competence is also better developed. Character is an affective domain, the design of the Industrial Work Culture Character Instrument (IKBKI) in carrying out this study was limited to five characters, namely: discipline, hard work, honesty, responsibility, and entrepreneurship.